KOMPOR BATOK KELAPA BERTEKANAN - Azharuddin, Azharuddin (AUSTENIT, 2009)
Fuel is important thing that is used in industries and home. However, if fuel is used in many sectors, it will be decrease. So, the writer design and make stoves that use coconut skin. The specification of stove is 48 cm height, 31 cm diameter. This stove has a control of pressure to add the pressure of stove when it is used. To boil the water this stove need 20 minutes and can reach the maximum temperature is about 610 o C